2014
DOI: 10.1002/jts.21900
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury, PTSD, and Current Suicidal Ideation Among Iraq and Afghanistan U.S. Veterans

Abstract: Suicide is a prevalent problem among veterans deployed to Iraq and Afghanistan. Traumatic brain injury (TBI) and psychiatric conditions, such as posttraumatic stress disorder (PTSD), are potentially important risk factors for suicide in this population, but the literature is limited by a dearth of research on female veterans and imprecise assessment of TBI and suicidal behavior. This study examined 824 male and 825 female U.S. veterans who were enrolled in the baseline assessment of the Veterans After-Discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 15 publications
7
55
0
Order By: Relevance
“…A study of 161 U.S. military personnel referred to a TBI clinic in Iraq for suspected head injury found that multiple episodes of TBI, which were common among U.S. military personnel, were associated with increased risk for lifetime suicidal thoughts and behaviors, as well as for current suicidal ideation (11). Baseline assessment of the Veterans After-Discharge Longitudinal Registry (Project VALOR), an observational registry of over 1,600 veterans with and without PTSD who deployed in support of the wars in Iraq and Afghanistan and were enrolled in the Veterans Affairs health care system, found that a history of TBI was associated with increased risk for current suicidal ideation, though only in men (9). The present longitudinal cohort study failed to clearly demonstrate an increase in risk for suicidality in individuals who sustained TBI during deployment.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 161 U.S. military personnel referred to a TBI clinic in Iraq for suspected head injury found that multiple episodes of TBI, which were common among U.S. military personnel, were associated with increased risk for lifetime suicidal thoughts and behaviors, as well as for current suicidal ideation (11). Baseline assessment of the Veterans After-Discharge Longitudinal Registry (Project VALOR), an observational registry of over 1,600 veterans with and without PTSD who deployed in support of the wars in Iraq and Afghanistan and were enrolled in the Veterans Affairs health care system, found that a history of TBI was associated with increased risk for current suicidal ideation, though only in men (9). The present longitudinal cohort study failed to clearly demonstrate an increase in risk for suicidality in individuals who sustained TBI during deployment.…”
Section: Discussionmentioning
confidence: 99%
“…The Center also reported that, since 2000, a total of 320,344 U.S. military personnel worldwide have had a medical diagnosis of TBI. Wisco et al (2014) found that U.S. veterans who had experienced multiple TBI incidents and those who had experienced a loss of consciousness due to TBI were significantly more likely to report suicidal ideation than those who had a single TBI and those who had no loss of consciousness. They also found that male veterans had a significantly higher risk of suicidal ideation following TBI, but female veterans did not.…”
Section: The Traumatic Brain Injury Epidemicmentioning
confidence: 96%
“…Moreover, there is a high level of co-occurrence of TBI and PTSD in this population. Many observational studies from both military and civilian settings (Hoge et al, 2008;Schneiderman et al, 2008) have firmly established an association between mTBI and PTSD (Hoge et al, 2008;Schneiderman et al, 2008;Carlson et al, 2011;Hart et al, 2014;Stein and McAllister, 2009;Tanev et al, 2014;Wilk et al, 2012;Wisco et al, 2014;Yurgil et al, 2014). These observations signal not only a need for effective interventions for PTSD and mTBI occurring individually, but for interventions that have the potential to address both conditions at the same time.…”
Section: Introductionmentioning
confidence: 99%